PERBANDINGAN EFEKTIVITAS TOPIRAMAT 50MG DAN TOPIRAMAT 100MG PADA PASIEN MIGREN - Locie, Henny Anggraini Sadeli, Nurdjaman Nurimaba (Neurona Majalah Kedokteran Neuro Sains, 2014)
INTRODUCTION MIGRAINE IS A RECURRENTEPISODIC PRIMARY HEADACHE THAT OFTEN CAUSE DISABILITY MIGRAINE PREVENTIVE THERAPY IS GENERALLY CONSTRAINED BY THE PRESENCE OF SIDE EFFECTS AND TOLERABILITY OF THE DRUG TOPIRAMATE 100MGDAY IS USED AS A PREVENTIVE MIGRAINE THERE IS NO TRIAL DOSE FOR INDONESIAN PEOPLE CONSIDERING THE GENETIC POLYMORPHISM AND WEIGHT DIFFERENCE OF WESTERN PEOPLE